Timed bright-light exposure and complaints related to shift work among women - Leppämäki, Sami; Partonen, Timo; Piiroinen, Pauliina; Haukka, Jari; Lönnqvist, Jouko (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This field study measured whether repeated, brief exposures to bright light during night shifts improved subjective well-being during and after night work. A secondary objective was to investigate whether this response differed by season (summer or winter), seasonality, or age. ' ' METHODS ': 'Eighty-seven healthy female nurses were voluntarily exposed to brief periods (4 x 20 minutes) of bright (5000 lux) light at scheduled times during every night shift over a 2-week period. Each morning following a night shift the subjects filled out self-assessment questionnaires measuring subjective symptoms and distress caused by work at night. The questionnaires were also completed 2 weeks before and after the light intervention. The study had two phases, summer (May-June) and winter (November-December). Thirty-seven of the subjects participated during both periods. ' ' RESULTS ': 'Light significantly alleviated the subjective distress associated with nightshift work, both in summer and in winter, independent of the subject`s age. The effect was stronger for those who reported routine seasonal changes in mood. ' ' CONCLUSIONS ': 'Short pulses of timed bright-light exposure may enhance subjective adaptation to night work.
Keywords: bright-light exposure; circadian phase; phototherapy; seasonality; shift work; woman